The Relationship Between the Quality of Sustainability Reporting and Corporate Financial Performance: A Cross-Sectional and Longitudinal Study - Sze Wing Amy Lee; Marcus Rodrigs; Thurai Murugan Nathan; Md. Abdur Rashid; Abdullah Al-Mamun (Australasian Accounting, Business and Finance Journal, 2023)
Purpose- The purpose of this paper is to examine the relationship between the quality of sustainability reports (QSR) and corporate financial performance (CFP). Since the global reporting initiative (GRI) reporting guideline is widely adopted by organizations over the world, the reporting organizations that report their corporate social responsibility (CSR) information under GRI reporting guidelines. Design/methodology/approach- In this study total of 6,519 samples are obtained from the GRI report list in the reporting period from the year 2009 to 2013 for analysis. Findings- The results demonstrate higher QSR results in better profitability and CFP but QSR exceeding a certain level in return increase the utilization of the firm’s resources and this leads to a decrease in overall profitability. Besides, the study proved that continuing investment in sustainability reporting and the decrease in a firm’s profitability affect the overall profitability – Returns on asset (ROA) and Returns on sales (ROS) of the organization. Originality/value- Provides the empirical study on the relationship between QSR and CFP based on the GRI report list in the reporting period from 2009 to 2013.
Keywords: Quality Sustainability Reporting; Corporate Financial Performance; Global Reporting Initiative; profitability; GRI reporting guidelines